Servicing satellite TV equipment - Beer, Nick (Newnes, 1998)
This is the definitive practical guide to fault-finding, troubleshooting and servicing satellite television equipment, both indoors and outdoors. It will take you through all areas of satellite television system servicing from the simplest fixed dish to fully motorised systems. From PAL to Mac to MPEG all contemporary systems are covered. Satellite TV systems have been installed in a wide variety of locations, using a bewildering range of equipment. That equipment is beginning to need maintenance and repair. To cope with the volume and variety of work, Nick Beer has written the first gu.